Efficacy of combined treatment of distal polyneuropathy in patients with type 2 diabetes mellitus and concomitant primaryhypothyroidism - Inessa Ivanovna Dubinina; Tatiana Vladimirovna Karapysh; Nina Fedorovna Nosova (Сахарный диабет)
Aim. To study changes of metabolic parameters and neurologic manifestations in patients with type 2 diabetes mellitus and concomitant primaryhypothyroidism under effect of combined therapy. Materials and methods. 62 patients with distal neuropathy (DN) including 16 with DM2 and primary hypothyroidism (PHT) (group 1), 32 DM2patients without thyroid pathology (group 2), and 15 patients with PHT without DM (group 3). The patients were matched for age and durationof all above diseases. They were treated by alpha lipoic acid-based drugs: thioctacid, thiogamma, berlithion, octolipen (600 U/d i/v), vitamins B:milgamma, combilipen (2 ml/d i/m) for 12 weeks. All measurements were made at admittance, 21 days and 12 weeks after it. The efficacy of therapywas estimated from changes in HbA1c levels, fasting and postprandial glycemia, lipid metabolism. DN was diagnosed using NSS, TSS, NDS, NDSm,and NIS-LL scales. Results. Combined therapy of patients with DM2 and PHT resulted in a decrease of HbA1c levels within 12 weeks, fasting and postprandialglycemia within 21 and 12 weeks respectively. Compensation of PHT led to a decrease of total cholesterol and triglyceride levels within 12 weeks.Subcompensation of carbohydrate metabolism (postprandial glycemia) improved neurologic symptoms within 21 weeks in all patients (NSS and TSSscales). The same effect was documented within 12 weeks in patients without thyroid pathology (NSS, TSS, NDS, NDSm, and NIS-LL scales). Inthose with PHT beneficial effect was revealed only using the NIS-LL scale. The worst outcome of therapy estimated from NSS, TSS, NDS, NDSm,and NIS-LL scales was documented in patients with DM2+PHT probably due to additional effect of thyroid pathology on the severity of DN. Conclusion. The use of NSS, TSS, NDS, NDSm, and NIS-LL scales makes it possible to reveal changes in the severity of sensorimotor disturbancesin DN patients depending on metabolic parameters modified by pathogenetic therapy.